MHD natural convection in saturated porous media with heat generation/absorption and thermal radiation: closed-form solutions - Turkyilmazoglu, M. (Archives of Mechanics, 2019)
The present work is devoted to the free convection flow occurring about a heated vertically stretching permeable surface placed in a porous medium under the influence of a temperature dependent internal heat generation or absorption. There are volume radiative heat sources in the fluid and the system is permeated by a uniform magnetic field. It is shown that the governing equations are reducible to a self-similar nonlinear ordinary differential equation of third order whose solutions are constructed analytically in the purely exponential series form. Under special circumstances, closed-form solutions are available which clearly indicate the existence of dual natural convection solutions. Otherwise, analytical solutions are still possible which are shown to be computed from an elegant algorithm without a need to invoke any numerical means. Exact solutions demonstrate, in physical insight that, in the presence of a heat sink absorbing the temperature from the porous medium increases the rate of heat transfer from the wall, whereas a heat source mechanism will surely overheat the system during the wall heating process, resulting in poor heat transfer rates. The presented exact solutions are beneficial for investigation of free convection phenomena in different geometries taking into account more complex physical features in higher dimensions.